Kepuasan Kerja Sebagai Pemediasi Pada Pengaruh Leader Member Exchange dan Pemberdayaan Terhadap Kinerja - Upik Handayani; Euis Soliha (Journal of Economics and Business, 2020)
Good governance is an understanding or basis for the accountability of performance of government agencies. Good governance has a meaning as good management or utilization which is expected to be a good performance achievement. Referring to the phenomenon that there is a decrease in performance in the East Semarang Subdistrict in Semarang City and there are still differences in the results of previous research on Member Exchange Leaders and Empowerment with its effect on performance, the research problem formulated is "How to improve performance through the Exchange Member Leader approach and Empowerment through job satisfaction as mediation? Data on Member Exchange Leaders, Empowerment, Job Satisfaction and Performance were obtained through interviews using questionnaires to 123 employees in the East Semarang District of Semarang City. The data obtained are then analyzed using the Multiple Regression Test carried out through the SPSS program. The results of the data analysis show that Member Exchange and Empowerment Leaders have a positive and significant effect on Work Head and Performance. Job Satisfaction has a positive and significant effect on performance. Member Exchange Leaders are more effective in indirectly influencing performance through job satisfaction and Empowerment more effectively the indirect effect on performance through job satisfaction.